Comprehensive evaluation of tumor response better evaluates the efficacy of neoadjuvant chemotherapy and predicts the prognosis in gastric cancer - a post hoc analysis of a single-center randomized controlled trial - Xuejun Gan; Yongning Jia; Fei Shan; Xiangji Ying; Shuangxi Li; Yan Zhang; Fei Pang; Ziyu Li (BMC Cancer)
Abstract Background Perioperative chemotherapy combined with D2 radical gastrectomy has been proven to be the standard treatment for local advanced gastric cancer. However, tumor regression grading (TRG) is the only neoadjuvant chemotherapy (NACT) response evaluation criterion recommended by the NCCN guideline for gastric cancer (GC). Given TRG’s limitations, we aim to explore a better comprehensive response evaluation method in this study. Methods Clinical information of 96 GC patients who received NACT was collected prospectively. Clinicopathological variables predictive of the response to NACT were identified by comparing the pre- and post-NACT examination results. The correlations between the response mode and long-term survival rate were assessed. Results Univariate Cox regression analysis showed that CT-based evaluation of the primary lesion thickness (CT-thickness) and tumor markers (TMs) were significantly associated with prognosis. The comprehensive evaluation method, including CT-thickness, TRG, and TMs, was constructed and proved to have a higher Harrell’s C index. Significant differences in overall survival (OS) and recurrence-free survival (RFS) were observed between responders and non-responders distinguished by the comprehensive evaluation method. Conclusions The combination of CT-thickness, TRG, and TMs could be used to construct a pragmatic NACT efficacy evaluation method with both high sensitivity and specificity, which could facilitate clinical decision-making, NACT-related clinical research conduction, and efficacy predictive biomarker exploration.